Analisis Kritis Pemikiran Wahbah Az-zuḥailī tentang Penetapan Talak - Abdul Khair (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2016)
This title of this article is An Analysis of Critical Thought Wahbah az-Zuḥailī Concerning Determination Separations. The purpose of this article was to assess the Wahbah az-Zuḥailī thinking about the establishment of divorce, legal istinbath methods used, as well as the relevance of thought Wahbah az-Zuḥailī the context of divorces in Indonesia. The results of the article showed that the determination of divorce divided into two divorces that do not require a court judgment and divorce which require a court decision. Separations that do not require a court decision is divorce by pronouncing talak and khuluk. While divorce is a divorce requires a court decision that caused his wife to go to court and divorce ta'asuf .The underlying thought Wahbah az-Zuḥailī are the legal consequences of divorce and the seat of the court as an institution that handles divorce cases. Law istinbath method used is based on the HR at-Tirmidhi about divorce joke, Bukhari about the events of Ibn Umar that mentalak his wife in a state of menstruation, QS. al-Baqarah verse 231 and HR Ibn Majah on the prohibition of doing immorality. Relevance thought Wahbah az-Zuḥailī the context of divorces in Indonesia can be seen in ta'asuf divorce procedures and the validity of divorce outside the court on condition that the assembly had dug legal facts that can be used as strong evidence for a divorce.